Risk identification for an information security management system implementation - Ramli, Noraza; A. Aziz, Normaziah (2012)
ISO/IEC 27001 is an international standard that provides a set of requirements for an Information Security Management System (ISMS) implementation. A risk assessment exercise for an ISMS implementation requires human expertise with comprehensive understanding and considerable knowledge in information security. A common risk assessment exercise is based on three sub-processes, namely, risk identification, risk analysis and risk evaluation. The lack of tools especially in the automation of risk identification emphasized the need of experienced personnel and this becomes a challenge for organizations seeking compliance with the ISMS standard. This paper proposes a relationship concept in asset and threat identification which is part of the risk identification sub-process. The concept provides a foundation to automate the risk assessment process for an identified scope of an ISMS implementation.